A Promising Insight into the Treatment of Triple-negative Breast Cancer with Curcumin loaded 1,4-Bis(3-aminopropyl) Piperazine Functionalized-graphene Quantum Dots: Synthesis, Cytotoxicity and In Silico Analyses - Alver, Dilara; Sen, Pinar; Azarkan, Serap Yalcin; Sakar, Dolunay; Konuk, Muhsin (SPRINGER, 2026)
Triple-negative breast cancer (TNBC) is a clinical problem because of its poor prognosis, aggressive behavior, and lack of targeted therapies. Thus, there is an urgent need to find effective evolving therapies that are specific and have few adverse consequences for triple-negative breast cancer. This study aimed to demonstrate that curcumin (Cur), which is the active ingredient of turmeric and is known to exhibit various biological properties, was conjugated to graphene quantum dots (GQDs), resulting in curcumin-loaded GQDs (Cur-GQDs) to overcome its poor solubility properties that limit its pharmacological potential, leading to high anticancer activity compared to curcumin alone. This conjugation (Cur-GQDs) was performed through pi-pi stacking, forming negatively charged and monodisperse supramolecular hybrids in aqueous solution. Molecular docking analyses revealed that Cur-GQDs structures exhibit high binding affinity against various cancer-related target proteins, and this binding shows a strong correlation with the observed anticancer activity. Additionally, in vitro cytotoxicity and cell migration tests performed on the MDA-MB-231 cell line, which is used as a TNBC cell model, showed that Cur-GQDs produced significantly higher anticancer effects compared to free curcumin application. The findings suggest that combining curcumin with nanotechnological carrier systems like GQDs could be a promising strategy to increase therapeutic efficacy and reduce side effects in the treatment of TNBC. This study demonstrates that the combination of natural compounds with nanostructures can be considered an innovative approach in difficult-to-treat cancer subtypes such as TNBC.
Keywords: Curcumin; Graphene quantum dot; Breast cancer; Triple breast cancer; MDA-MB231; SOLUBILITY; FAMILY; Pharmacology & Pharmacy